Diverging olfactory sensitivities to yeast volatiles reflect resource partitioning of tephritids and drosophilids - Biasazin, Tibebe Dejene; Herrera, Sebastian Larsson; Kimbokota, Fikira; Dekker, Teun (Frontiers in Ecology and Evolution, 2022)
As pests of fruits and vegetables, ovipositing tephritid fruit flies are infamous for their frugiphily. Yet, adult tephritids have remained saprophilic in their feeding behavior, as they require decomposing, protein rich media for sexual maturation and oogenesis. Drosophilid fruit flies, in contrast, are saprophilic both during oviposition and feeding. Here we compared the sensory and behavioral responses of two tephritid (Bactrocera dorsalis and Ceratitis capitata) and two drosophilid species (Drosophila melanogaster and Drosophila suzukii) to differentially aged cultures of the yeast Saccharomyces cerevisiae. We assessed convergence and divergence in the detection of and behavioral response to these attractive substrates, and how these might be linked to the roles of the substrates for the different taxa. The headspace shifted substantially as broth cultures transitioned from active (1-day) to inactive (8- and 15-days). Interestingly, Drosophila flies were significantly attracted to actively fermenting 1-day old yeast cultures, whereas the preference shifted to older cultures for the tephritids. B. dorsalis flies in particular preferred inactive, lysing cultures (8- and 15-days old). We identified compounds from the 1-day and 8-days old broth cultures that elicited antennal responses in each species. Synthetic blends composed of antennally-active compounds evoked similar behavioral responses as broth cultures. Similarly, the attractiveness of less attractive broth cultures (1-day and 8-days old for drosophilids and tephritids, respectively) could be augmented by adding volatiles of the more attractive cultures. The results show that the volatile profiles of fermenting substrates evolve quantitatively and qualitatively, and that fly species key into volatile blends that indicate suitability of the substrates for their purposes. For drosophilids early arrival at fermenting substrates confers a competitive advantage to offspring. In contrast, for tephritid the concentration and availability of protein is facilitated by older, lysed yeast cultures. The data from this comparative study are also instrumental in the development of novel lures for these pests.